Macroalgae Community Structure at Semak Daun Island, Kepulauan Seribu, Indonesia - Sekar Ajeng Wulandari; Bintang Marhaeni; Maria Dyah Nur Meinita (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
Semak Daun Island was part of the Kepulauan Seribu which was a marine tourism destination such as snorkeling and diving site. The existence of these activities had been affecting the condition of the biota community that lives in these waters including macroalgae. The condition of macroalgae communities can be observed by abundance, diversity, uniformity and dominance analysis that occur in these communities that are known as the community structure. The purpose of this study was to determine the structure of macroalgae communities (abundance, diversity, uniformity and dominance) in Semak Daun Island. This research results was found 3 divisions, 10 orders, 13 families, 15 genera and 20 species of macroalgae. The abundance of macroalgae ranges from 235 - 782 individuals/100m2, classified as low abundance. Diversity ranges from 0.96 to 1.83, classified as low diversity. Uniformity ranges from 0.4 to 0.71, including the moderate uniformity and Dominance ranges from 0.22 to 0.57 belong to the low to moderate category, with the most dominant species being Galaxaura rugosa. Physics-chemical parameters of water in general are included in the normal range to support macroalgae life. Based on this, the condition of the macroalgae community structure on Semak Daun Island which is in a less favorable condition is likely due to the existence of snorkeling and diving activities by tourists. Keywords: community structure, macroalgae, Semak Daun Island